Informatics to support tactics and strategies in curling - Masui, F.; Hirata, K.; Otani, H.; Yanagi, H.; Ptaszynski, M. (International Journal of Automation Technology, 2016)
This paper presents game information analysis by utilizing a digital scorebook system, as the first tool for curling informatics, which supports coaches and players in realizing smart tactics and strategies in the sport of curling. Our research project, called "Curling Informatics," aims to develop an environment to support curling strategies and tactics by realizing methods to record game information, perform analysis, and provide visualization and sharing of the information. We found a significant correlation between the differences in shot accuracies and scores from game information collected by our digital scorebook system for more than 200 games played by the Japanese national class. The results suggest that the difference in shot accuracies is related to the difference in game scores. This is valuable new knowledge to support strategic/tactical planning in curling games. However, the correlation for games involving world-class teams becomes weaker than for the Japanese national class because there is scarcely any difference in shot accuracies.